(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2026)
Forts are the part of our heritage they were the centres of administration, military power, religion, culture and economic activities in old days. Conservation of forts means preservation of our heritage sites. The National Disaster Management Guidelines for Cultural Heritage Sites and Precincts issued by National Disaster Management Authority in 2017. In the light of these guidelines Kolhapur District Disaster Management Authority have prepared Panhala Fort Disaster Management Plan. It is novel step taken by the Kolhapur District Disaster Management Authority which should be followed by the other states. In this backdrop author has mentioned that six series of forts from the state of Rajasthan (in 2013) and twelve Maratha Military Landscape Forts are recently declared as World Heritage Site. So, there is need to prepare fort specific disaster management plan by concern authority in order to conserve our rich heritage as well as to ensure the safety of visitors. Preparation of such plan is an opportunity to inculcate global initiatives of disaster management at the local level.